Attitudes toward hearing aid use in the general adult Jordanian population - Jarrar, M.D, Saba; Obaidi, M.D., Yazan Al; Alaidy, M.D , Hamadeh; Shahade, M.D , Izz-Aldeen; Alsholi, M.D , Mohammed; M.D , Leen Alnaser; Alkhalaileh, M.D, Salam; Aljaber, M.D, Bayan; Al-Ghwairy, M.D, Lara; Alabbadi, M.D, Shames; et al. (Journal of Neonatal Surgery, 2025)
Background: Despite the rising global prevalence of hearing loss, hearing aid adoption remains low, often due to stigma and misconceptions. Understanding public perceptions is critical to improving hearing health outcomes. Methods: This cross-sectional study surveyed 678 adults in Jordan between October 2024 and February 2025. Participants were recruited from universities, hospitals, and public areas across the country. An Arabic-language questionnaire adapted from validated tools was used to assess awareness, attitudes, and social stigma toward hearing aids. Demographic variables included age, gender, education, and income. Results: The sample included 46.9% males and 53.1% females, with most aged 18–75 years and a majority having a college-level education. Overall awareness of hearing aids was high and increased with age and income. While most participants had a positive attitude toward hearing aid use, some negative views persisted—particularly among women who prioritized appearance and men who reported lower willingness to wear hearing aids. Misconceptions were more common in lower-income groups. Social stigma was generally low but higher among younger and lower-income individuals. All observed associations were statistically significant (p < 0.05). Conclusion: While awareness and attitudes toward hearing aids are generally positive in Jordan, notable misconceptions and stigma remain among specific demographic groups. Targeted public health campaigns and educational initiatives are essential to reduce stigma and improve access and acceptance of hearing aids.